Retaining Teachers: Intentional Invitational Action and Social Justice Leadership as Driving Forces - Martin, Barbara N; McDowell, William (Advances in Social Sciences Research Journal, 2021)
Social justice challenges and teacher retention challenges create crises in urban school districts across the United States. Moreover, despite literature linking principal leadership with school ethos known is little as to how the use of an invitational leadership style with a social justice orientation has a connection to the retention of teachers in urban settings. This study used a qualitative case study survey design conducted at two urban school district settings, one in the Western United States and the other in the Midwest. The analysis found a connection between the principal using an invitational leadership style, and the presence of a strong social orientation that helped to retain teachers. These findings present implications for scholars and practitioners.